Pengaruh Variasi Produk Dan Kemasan Terhadap Keputusan Pembelian - Jilan Nabila Hajarakhuwailid; Hartanti Nugrahaningsih; Leny Muniroh (Indonesian Journal of Innovation Multidisipliner Research, 2024)
Competition in the bakery world is getting tighter day by day, not only from big players but also from small players in the home bakery industry who are also enlivening the bakery business world. There are many ways that must be done to win the competition or to survive. The aim of this research is to find out whether product and packaging variations are factors that can influence purchasing decisions or not. After conducting research, using the Structural Equation Model (SEM) method using the SmartPLS 4 application. The results of this research are that product and packaging variations have a simultaneous effect on purchasing decision variables, then the coefficient of the relationship between product variations and purchasing decisions shows a significant influence, and the coefficient of the relationship between packaging and purchasing decisions shows that packaging has a positive and significant effect